Combined NMDA Inhibitor Use in a Patient With Multisubstance-induced Psychotic Disorder. Issue 3 (May 2018) - Caloro, Matteo; Calabrò, Giuseppa; de Pisa, Eleonora; Rosini, Enrico; Kotzalidis, Georgios D.; Lonati, Davide; Locatelli, Carlo Alessandro; Papa, Pietro; Schifano, Fabrizio; Girardi, Paolo
Abstract : N/A: Novel psychoactive substance use is a major social concern. Their use may elicit or uncover unpredictably as yet undescribed clinical pictures. We aimed to illustrate a multisubstance use case indistinguishable from paranoid schizophrenia, so to alert clinicians on possibly misdiagnosing substance-induced psychotic disorders. Case report: We describe a case of a 32-year-old man who started at 18 years with cannabinoids and ketamine, and is currently using N -methyl-D-aspartate (NMDA) antagonists. At age 23, he developed social withdrawal after being assaulted by a stranger, but did not consult psychiatrists until age 26; during this period, he was using internet-purchased methoxetamine and ketamine, and was persecutory, irritable, suspicious, and insomniac and discontinued all received medical prescriptions. He added dextromethorphan to his list of used substances. At age 31, while using phencyclidine, and, for the first time, methoxphenidine, he developed a religious delusion, involving God calling him to reach Him, and the near-death experiences ensured by NMDA antagonists backed his purpose. He received Diagnostic and Statistical Manual of Mental Disorders, 5th Edition diagnosis of multisubstance-induced psychotic disorder and was hospitalized 8 times, 6 of which after visiting the emergency room due to the development of extreme anguish, verbal and physical aggression, and paranoia. He reportedly used methoxphenidine, methoxyphencyclidine, ethylnorketamine, norketamine, and deschlorketamine, to achieve near-death experiences, and eventually to reach God in heavens. Conclusions: This case points to the need for better control of drugs sold on the internet. It also illustrates that people using NMDA antagonists may present clinical pictures indistinguishable from those of major psychoses and are likely to be misdiagnosed. Abstract : Supplemental Digital Content is available in the text